2011
DOI: 10.1093/nar/gkr118
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PvuRts1I endonuclease as a tool to investigate genomic 5–hydroxymethylcytosine

Abstract: In mammalian genomes a sixth base, 5-hydroxymethylcytosine (hmC), is generated by enzymatic oxidation of 5-methylcytosine (mC). This discovery has raised fundamental questions about the functional relevance of hmC in mammalian genomes. Due to their very similar chemical structure, discrimination of the rare hmC against the far more abundant mC is technically challenging and to date no methods for direct sequencing of hmC have been reported. Here, we report on a purified recombinant endonuclease, PvuRts1I, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 33 publications
1
48
0
2
Order By: Relevance
“…The PvuRts1i enzyme cuts 12-15 nucleotides away from the 5hmC sites. 33 Therefore, regions which show significantly higher coverage compared to the surrounding noise levels (also called peaks) are indicative of the presence of 5hmC within § 12-15 nucleotides from the genomic location of the peaks. 25 We found that Pvu-Seq can only validate the presence or absence of 5hmC site (s) and cannot be used quantitatively at the sequencing depth that we used in this paper.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PvuRts1i enzyme cuts 12-15 nucleotides away from the 5hmC sites. 33 Therefore, regions which show significantly higher coverage compared to the surrounding noise levels (also called peaks) are indicative of the presence of 5hmC within § 12-15 nucleotides from the genomic location of the peaks. 25 We found that Pvu-Seq can only validate the presence or absence of 5hmC site (s) and cannot be used quantitatively at the sequencing depth that we used in this paper.…”
Section: Resultsmentioning
confidence: 99%
“…69 DNA digestion with PvuRst1L and DNA sequencing PvuRts1I (Pvu) restriction enzyme can directly cleave hydroxymethylated DNA 12-14 bps away from the 5hmC site. 33 We developed a new technique that we call Pvu-seq which allows direct detection of 5hmC without chemical modification of 5hmC or bisulfite conversion. A paper describing this technique was published in BMC Genomics.…”
Section: Hm450k Bead Chip Arraymentioning
confidence: 99%
See 1 more Smart Citation
“…[32] Furthermore, the endonuclease PvuRts1l has been identified to specifically act on hmC. [33] In the future, nanopore sequencing might be a solution to the problem. First studies showed that this sequencing method is indeed able to distinguish between mC and hmC in both single-and double-stranded DNA.…”
Section: Site-specific Detection Of 5-hydroxymethylcytosinementioning
confidence: 99%
“…[32] Zusätzlich wurde die Endonuklease PvuRts1l identifiziert, die spezifisch auf hmC wirkt. [33] In Zukunft könnte Nanoporensequenzierung eine Lösung für dieses Problem sein. Erste Untersuchungen zeigten, dass diese Sequenzierungsmethode zwischen mC und hmC in Einzel-und Doppelstrang-DNA unterscheiden kann.…”
Section: Positionsspezifische Detektion Von 5-hydroxymethylcytosinunclassified